Hiperamonemia ativa HIF-1α pela via NF-kB : um possível mecanismo de sarcopenia em cirrose - Silva, Rafaella Nascimento e (2016)
Hyperammonemia impairs skeletal muscle protein synthesis and induces autophagy by upregulating myostatin via nuclear factor-kappaB (NF-kB). Skeletal muscle ammonia metabolism occurs via synthesis of glutamate and glutamine via critical TCA intermediate α-KG, that regulates increase expression of hypoxia inducible factor 1α (HIF-1α). Furthermore, there is a interaction between HIF-1α and NF-kB. Objective: This study evaluated the effects of hyperammonemia in NF-kB and HIF-1α cross-talking. Methods: To examine the effects of ammonium acetate intervention under HIF-1α signaling through NF-kB pathway it has generated a stable knockdown cell line for NFkB and the subunits α and β of the I kappa B kinase (IKK) complex (IKKα and IKKβ) evaluating the HIF-1α and myostatin activities. Results: The protein expression of HIF- 1α was significantly higher in C2C12 murine myotubes under ammonium acetate intervention compared to control. Once the deletion of NF-kB, IKKα and IKKβ occurs, the HIF-1α is not expressed, suggesting a cross-talking between them. The protein expression of myostatin was significantly higher in C2C12 IKKα deletion under ammonium acetate intervention compared to C2C12 random suggesting that myostatin is not IKKα dependent. Conclusion: We conclude that hyperammonemia is a normoxemic activator of HIF-1α through NF-kB pathway that results in sarcopenia via up-regulation of myostatin expression.